Rutile-phase TiO2@carbon core-shell nanowires and their photoactivation in visible light region - Saravanan L.; Patil R.A.; Gultom P.; Kumar B.; Manikandan A.; Fu Y.-P.; Chueh Y.-L.; Cheng C.-L.; Yeh W.-C.; Ma Y.-R. (My University, 2025)
Titanium dioxide (TiO2) has been acknowledged as one of the efficient photocatalysts in the UV region. To extend the photo-absorption region toward visible lights, the TiO2 nanowires enclosed with carbon shells (TiO2@carbon core-shell nanowires) were synthesized by a chemical vapor deposition technique at various temperatures from 650 to 950 °C. The transmission electron microscopy (TEM) and X-ray diffraction (XRD) analyses revealed that TiO2 cores and carbon shells are rutile and graphitic structures, respectively. From Raman spectra, the peak intensity of the Eg mode was observed to be redshifted with elevated growth temperatures due to the increase in oxygen vacancies in the TiO2@carbon core-shell nanowires. From X-ray photoelectron spectroscopy (XPS) results, the oxygen vacancies were strongly related to the Ti3+ ions. The UV–visible spectroscopic studies show a possible decrease in photocatalytic energy from 3.1 to 2.7 eV for the TiO2@carbon core-shell nanowires, indicating that the light absorption was enhanced in the visible-light region. The optical absorbance results confirmed the presence of the mid-gap states due to the oxygen vacancies, which are responsible for the visible-light absorption. The photocatalytic activity of the TiO2@carbon core-shell nanowires studied by methylene blue (MB) dye degradation is effective under visible lights. © 2021 Elsevier Ltd